Class III β-Tubulin Expression Is of Value in Selecting nab-Paclitaxel and Gemcitabine as First-Line Therapy in Unresectable Pancreatic Cancer. Issue 4 (12th April 2022) - Kato, Akihisa; Naitoh, Itaru; Naiki-Ito, Aya; Hayashi, Kazuki; Okumura, Fumihiro; Fujita, Yasuaki; Sano, Hitoshi; Nishi, Yuji; Miyabe, Katsuyuki; Inoue, Tadahisa; Hirano, Atsuyuki; Takada, Hiroki; et al.
Abstract : Objectives: Nab -paclitaxel and gemcitabine (GnP) or FOLFIRINOX (a combination of leucovorin, fluorouracil, irinotecan, and oxaliplatin [FFX]) is currently recognized as the standard first-line regimen for unresectable pancreatic ductal adenocarcinoma (PDAC). Class III β-tubulin (TUBB3) has the potential to predict resistance to taxane in various tumors; therefore, this study aimed to clarify whether TUBB3 is a predictive marker for GnP response. Methods: We retrospectively reviewed 113 patients with PDAC who received GnP or FFX as first-line chemotherapy and examined immunohistochemically the TUBB3 expression in specimens obtained by endoscopic ultrasound-guided fine-needle aspiration. Results: High TUBB3 expression was associated with a significantly lower disease control rate ( P = 0.017) and shorter progression-free survival (PFS) ( P = 0.019), and multivariate analysis revealed that TUBB3 expression was an independent variable for PFS in the GnP first-line group ( P = 0.045). In addition, in the FFX first-line group, TUBB3 expression was not correlated with PFS or overall survival (OS). In all 113 patients, TUBB3 expression was not also associated with OS. Conclusions: Class III β-tubulin might be a predictive factor for the response of GnP, but not a prognostic factor for OS, helping the selection of an optimized first-line chemotherapy regimen for unresectable PDAC.